2022
DOI: 10.3390/ijms23074050
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Entry Inhibitors against Delta and Omicron Variants of SARS-CoV-2

Abstract: Entry inhibitors against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) are urgently needed to control the outbreak of coronavirus disease 2019 (COVID-19). This study developed a robust and straightforward assay that detected the molecular interaction between the receptor-binding domain (RBD) of viral spike protein and the angiotensin-converting enzyme 2 (ACE2) receptor in just 10 min. A drug library of 1068 approved compounds was used to screen for SARS-CoV2 entry inhibition, and 9 active drugs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Protein–protein docking studies pointed out in the same direction . There is undoubtedly well-built support for the importance of electrostatic interactions for this process which is constantly confirmed for the latest variants, ACE2 polymorphisms, and new studied Abs. ,,, Nevertheless, it is worth mentioning that Jawad and coauthors more recently added that the van der Waals interactions can also be critical to stabilizing the RBD-ACE2 complex even if the Coulombic interactions are the main driving force for the recognition process between the RBD and ACE2 . Some new all-atom MD works have shown that the presence of long glycans can enhance the RBD-ACE2 binding affinity .…”
Section: Introductionmentioning
confidence: 90%
“…Protein–protein docking studies pointed out in the same direction . There is undoubtedly well-built support for the importance of electrostatic interactions for this process which is constantly confirmed for the latest variants, ACE2 polymorphisms, and new studied Abs. ,,, Nevertheless, it is worth mentioning that Jawad and coauthors more recently added that the van der Waals interactions can also be critical to stabilizing the RBD-ACE2 complex even if the Coulombic interactions are the main driving force for the recognition process between the RBD and ACE2 . Some new all-atom MD works have shown that the presence of long glycans can enhance the RBD-ACE2 binding affinity .…”
Section: Introductionmentioning
confidence: 90%
“…56 There is undoubtedly well-built support for the importance of electrostatic interactions for this process which is constantly confirmed for the latest variants, ACE2 polymorphisms, and new studied Abs. 23,32,36,[57][58][59][60][61][62] Nevertheless, it is worth mentioning that Jawad and co-authors more recently added that the van der Waals interactions can also be critical to stabilizing the RBD-ACE2 complex even if the Coulombic interactions are the main driving force for the recognition process between the RBD and ACE2. 59 Although the main aspects are consistently reproduced, quantitative results for the predicted binding affinities can vary a lot as was critically discussed by Taka and colleagues.…”
Section: Introductionmentioning
confidence: 99%
“…The wild-type, alpha, delta, epsilon, and gamma variants of pseudotyped viral particles were obtained from RNAicore, Academia Sinica, Taiwan. The viral particles were prepared as reported earlier ( Lee et al, 2022 ). Briefly, the pseudotyped viral particles were obtained by co-transfecting Lenti-X 293T cells with transfer plasmid (pLAS2w.Nluc-T2A-RFP-C.Ppuro, 5 μg), packaging plasmid (pCMVdeltaR8.91, 4 μg), and 1 μg spike-expressing plasmid (wild type, alpha, delta, epsilon, and gamma variants of pcDNA3.1-2019-nCoV-S-d18 in a 10-cm culture dish.…”
Section: Methodsmentioning
confidence: 99%